Islam dan Kebudayaan - Nadhuha, Nadhuha; Alpizar, Alpizar (IAINU Kebumen, 2024)
The purpose of this research is to find out about Islam and culture. This research uses a qualitative research method with a descriptive approach, namely describing how Islam and culture are. The data analysis method used is content analysis, which relates to content containing about Islam and culture. The results of this research show that Islam and culture are different, but two things that cannot be separated. Religion without culture will die, and culture without religion will become blind and lose direction. So Islam and culture are interconnected, continuous with each other and influence each other. The functions of Islam and culture in daily life include mosques, how to dress and others.